90Y‐ibritumomab‐tiuxetan as a therapeutic alternative for follicular lymphoma (FL): A single‐center experience. (3rd September 2018) - Spukti, Eva U.; Schmidt, Lars Henning; Schulze, Arik; Schliemann, Christoph; Görlich, Dennis; Wardelmann, Eva; Hartmann, Wolfgang; Lenz, Georg; Berdel, Wolfgang E.; Kerkhoff, Andrea
Abstract: Background: Follicular lymphoma (FL) is the most frequent indolent lymphoma subtype in adults. Maintenance therapy with rituximab is frequently applied to FL patients with complete or partial response following initial chemoimmunotherapy. However, radioimmunotherapy with 90 Y‐ibritumomab‐tiuxetan represents a therapeutic alternative. Methods: To compare the clinical and the prognostic impact of both therapies, a study collective of n = 56 patients diagnosed with indolent B‐cell lymphoma was retrospectively investigated. The study collective was subdivided into two groups: n = 36 patients treated with rituximab maintenance therapy vs n = 20 patients treated with 90 Y‐ibritumomab‐tiuxetan. Results: No prognostic differences for performance status, FLIPI score, gender, or B‐symptoms were found for 90 Y‐ibritumomab‐tiuxetan or rituximab maintenance therapy. Overall survival rates and progression‐free survival did not differ between both maintenance therapies. Conclusion: Our retrospective single‐center analysis of two patient groups without major differences in prognostic parameters revealed similar outcome with two different maintenance therapies. Hence, 90 Y‐ibritumomab‐tiuxetan therapy might offer a valuable alternative treatment option for FL patients with partial response. However, large prospective trials are needed to confirm the reported findings.